A nano-improved black automobile coating and preparation method thereof

By using nano-improved black automotive coatings, combined with raw materials such as hydroxyacrylic resin and nano-silicon dioxide, the existing black automotive coatings have solved the problems of dirt retention, gloss reduction and poor friction resistance after rainy days, achieving higher oxidation resistance and friction resistance reduce the difficulty of cleaning and maintenance.

CN118909493BActive Publication Date: 2025-02-14YINGDE BANGSHI CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411065654.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-02-14
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The existing black automotive paints with resin as the main raw material are prone to dirt after rainy days, and the gloss is reduced due to the hydrophilicity and aging of the resin, poor friction resistance, and easy to cause paint loss and scratches.

Method used

Using nano-improved black automotive coatings, by using hydroxyacrylic resin, high-color carbon black, dispersant, mixed solvent, cellulose acetate butyrate, composite functional agent, defoaming agent, leveling agent, thickening agent and nano-dioxide Silicon and other raw materials are prepared to prepare a green and environmentally friendly automotive coating, and a nanocomposite liquid is formed through specific stirring and oscillation steps to improve the friction resistance and oxidation resistance of the coating.

Benefits of technology

It significantly improves the oxidation resistance and friction resistance of black automotive paint, reduces sewage adhesion, reduces the difficulty of cleaning and maintenance, and makes the paint more durable and aesthetic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004979279120000091
    Figure BDA0004979279120000091
Patent Text Reader

Abstract

The invention discloses a nano-improved black automobile coating and a preparation method thereof, belonging to the technical field of automobile coatings. The invention comprises the following raw materials in parts by weight: 62-73 parts of hydroxy acrylic resin, 1.8-2.2 parts of high-pigment carbon black, 1.8-2.2 parts of dispersant, 23-27 parts of mixed solvent, 6-8 parts of cellulose acetate butyrate, 4-6 parts of composite functional agent, 0.1-0.3 parts of defoamer, 0.1-0.3 parts of leveling agent, 0.8-1.5 parts of thickener and 1-3 parts of nano silicon dioxide; the automobile coating of the invention is further added with a self-made composite functional agent, the composite functional agent has a large number of phenolic hydroxyl groups and silaneoxy groups, can not only improve the oxidation resistance of the automobile coating, but also can convert the hydroxy acrylic resin in the raw materials from hydrophilic to hydrophobic, significantly improve the anti-fouling ability, and has excellent mechanical properties, and can be widely promoted and applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile coatings, and in particular to a nano-improved black automobile coating and a preparation method thereof. Background Art

[0002] Automotive coatings play an important role in the automotive industry. They have undergone a transformation from traditional oil-based coatings to modern environmentally friendly coatings. Although traditional oil-based coatings are brightly colored, they have the disadvantages of high volatile organic compound emissions and poor environmental performance. With the improvement of environmental awareness, environmentally friendly coatings with resin as the main raw material have gradually emerged. These new coatings not only reduce the emission of volatile organic compounds, but also have good corrosion resistance, bringing new impetus to the green development of the automotive coatings industry.

[0003] Among car coatings, black is a timeless classic color for car exteriors. Black car coatings have been widely recognized by car manufacturers for their ability to give cars a calm and atmospheric appearance. However, existing car coatings with resin as the main raw material have conspicuous dirt left on cars that have been in contact with rainy sewage after drying due to the hydrophilicity of the resin. This is particularly evident in black car coatings. At the same time, black absorbs all the light in the sun, so its temperature is usually higher than that of cars of other colors. The resin in the coating is also more likely to lose its gloss due to aging. In addition, car coatings are not resistant to friction, so paint peeling and scratches may occur after long-term use. The above shortcomings are all urgently needed to be solved by the automotive coatings industry. Summary of the invention

[0004] The object of the present invention is to provide a nano-modified black automobile coating and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A nano-improved black automobile coating comprises the following raw materials in parts by weight: 62-73 parts of hydroxy acrylic resin, 1.8-2.2 parts of high-pigment carbon black, 1.8-2.2 parts of dispersant, 23-27 parts of mixed solvent, 6-8 parts of cellulose acetate butyrate, 4-6 parts of composite functional agent, 0.1-0.3 parts of defoamer, 0.1-0.3 parts of leveling agent, 0.8-1.5 parts of thickener, and 1-3 parts of nano silicon dioxide;

[0007] The preparation method of the nano-improved black automobile coating comprises the following steps:

[0008] The first step is to weigh each raw material according to the mass fraction;

[0009] The second step is to stir and mix the nano-silicon dioxide, dispersant, composite functional agent and mixed solvent, and then add them into a high-speed oscillator for oscillation to obtain a nano-silicon dioxide dispersion;

[0010] The third step is to add the nano-silica dispersion, high-pigment carbon black, hydroxy acrylic resin, cellulose acetate butyrate, defoamer, and leveling agent into a dispersion tank and mix them evenly to obtain a nano-composite liquid;

[0011] Step 4, adding the thickener into the nanocomposite liquid, stirring and mixing to obtain the nano-improved black automobile coating;

[0012] Further, the high-pigment carbon black is one of Orilon FW255, Orilon FW200, and Columbia Carbon Black 5000;

[0013] Further, the dispersant is EFKA4310;

[0014] Further, the mixed solvent is one of butyl acetate, xylene, and propylene glycol methyl ether acetate;

[0015] Further, the thickener is Hemmings WT-105;

[0016] Furthermore, the defoaming agent is one of BYK-088 and BYK-054;

[0017] Furthermore, the leveling agent is Hemingway 837;

[0018] Furthermore, in the second step, the stirring time condition is 10-15 min, the stirring speed is 400 r / min, the high-speed oscillation time condition is 60-75 min, and the high-speed oscillation frequency is 640-660 times / min;

[0019] Furthermore, in the third step, the speed of the dispersion cylinder is set to 900-1000 r / min, and the dispersion time in the dispersion cylinder is 45-60 min;

[0020] Furthermore, the stirring speed of the nanocomposite liquid is 150 r / min, and the stirring time is 15-25 min;

[0021] Furthermore, the composite functional agent is prepared by the following steps:

[0022] Step 1, add phloroglucinol, epichlorohydrin and dimethyl sulfoxide into a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirrer, react at 60° C. for 5 h, and after the reaction is completed, perform rotary evaporation to obtain intermediate 1;

[0023] Step 2, add intermediate 1, phloroglucinol, sodium carbonate solution and dimethyl sulfoxide into a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirrer, and react at a temperature of 50-60° C. for 3 hours. After the reaction is completed, separate the organic layer with a separatory funnel and rotary evaporate to obtain intermediate 2;

[0024] Step 3, add intermediate 2 and concentrated sulfuric acid into a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirrer, and react at a temperature of 170° C. for 3 hours. After the reaction is completed, rotary evaporation is performed to obtain intermediate 3;

[0025] Step 4, adding toluene, intermediate 3 and platinum complex into a three-necked flask, installing a condenser and a thermometer, turning on a magnetic stirrer, heating to 110° C., and then dropping dimethoxymethylsilane thereinto using a high-pressure dropping pump. After the dropping is complete, reacting at a temperature of 140° C. for 1 hour, and rotary evaporating to obtain the composite functional agent;

[0026] Furthermore, the amount ratio of phloroglucinol, epichlorohydrin and benzene used in step 1 is 0.1-0.11 mol:0.1 mol:150-180 ml;

[0027] Furthermore, in step 2, the sodium carbonate solution is a sodium carbonate aqueous solution with a mass fraction of 50%, and the amount ratio of the intermediate 1, phloroglucinol, sodium carbonate solution and dimethyl sulfoxide used is 0.08 mol: 0.08-0.1 mol: 70 ml: 130 ml;

[0028] Furthermore, the concentrated sulfuric acid in step 3 is a sulfuric acid aqueous solution with a mass fraction of 98%, and the amount ratio of the intermediate 2 to the concentrated sulfuric acid is 0.07 mol:12-15 ml;

[0029] Furthermore, the amount ratio of toluene, intermediate 3, platinum complex and dimethoxymethylsilane used in step 4 is 35-40 ml:0.05 mol:1 ml:0.05 mol.

[0030] Beneficial effects of the present invention:

[0031] (1) The present invention uses hydroxy acrylic resin, high-pigment carbon black, dispersant, mixed solvent, cellulose acetate butyrate, composite functional agent, defoamer, leveling agent, thickener, and nano-silicon dioxide as raw materials to prepare a nano-improved black automotive coating. The automotive coating uses hydroxy acrylic resin as raw material and is green and environmentally friendly. The addition of nano-silicon dioxide has greatly improved the friction resistance.

[0032] (2) The present invention uses phloroglucinol and epichlorohydrin as raw materials, utilizes the phenolic hydroxyl group of phloroglucinol and the epoxy group of epichlorohydrin to undergo a ring-opening reaction to obtain intermediate 1, utilizes the chlorine atom of intermediate 1 and the phenolic hydroxyl group of phloroglucinol to undergo a bimolecular nucleophilic substitution reaction in a weakly alkaline environment of a sodium carbonate solution to obtain intermediate 2, utilizes the alcoholic hydroxyl group of intermediate 2 to eliminate under the catalytic action of concentrated sulfuric acid to obtain intermediate 3 containing a double bond structure, utilizes the double bond of intermediate 3 to undergo an addition reaction with dimethoxymethyl hydrogen silicon under the catalysis of a platinum complex to obtain a silane-modified composite functional agent, the composite functional agent contains 4 phenolic hydroxyl groups and has good antioxidant properties, the silane-modified composite functional agent has good hydrophobic properties and friction resistance, and in addition, the composite functional agent has both an inorganic (silane alkoxy) and an organic structure, and therefore can also form a strong interaction force at the interface between the hydroxy acrylic resin and the nano-silica, thereby playing a coupling role, so that the nano-silica can be more stably dispersed in the system, and the degree of combination between the nano-silica and the hydroxy acrylic resin is improved.

[0033] (3) The black automobile coating of the present invention is green and environmentally friendly, and has an elegant appearance. Due to the addition of the composite functional agent, the oxidation resistance and friction resistance of the black automobile coating are significantly improved, and the coating is durable. In addition, the automobile coating of the present invention is also hydrophobic, and sewage is not easy to adhere, which significantly reduces the difficulty of cleaning and maintenance. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The composite functional agent is prepared by the following steps:

[0037] Step 1, 0.1 mol phloroglucinol, 0.1 mol epichlorohydrin and 150 ml dimethyl sulfoxide are added into a container, stirred, reacted at 60° C. for 5 h, and after the reaction, rotary evaporation is performed to obtain intermediate 1;

[0038] Step 2, 0.08 mol intermediate 1, 0.08 mol phloroglucinol, 70 ml sodium carbonate solution with a mass fraction of 50% and 130 ml dimethyl sulfoxide are added into a container, stirred, and reacted at a temperature of 50° C. for 3 h. After the reaction is completed, the organic layer is separated by a separatory funnel, and the intermediate 2 is obtained by rotary evaporation;

[0039] Step 3, adding 0.07 mol of intermediate 2 and 12 ml of concentrated sulfuric acid into a container, stirring, reacting at a temperature of 170° C. for 3 h, and after the reaction, rotary evaporation to obtain intermediate 3;

[0040] Step 4, add 35 ml of toluene, 0.05 mol of intermediate 3 and 1 ml of platinum complex into a container, stir, heat to 110°C, add 0.05 mol of dimethoxymethylsilane, react at 140°C for 1 hour, and rotary evaporate to obtain the composite functional agent.

[0041] Example 2

[0042] The composite functional agent is prepared by the following steps:

[0043] Step 1, 0.105 mol phloroglucinol, 0.1 mol epichlorohydrin and 165 ml dimethyl sulfoxide are added into a container, stirred, reacted at 60° C. for 5 h, and after the reaction, rotary evaporation is performed to obtain intermediate 1;

[0044] Step 2, 0.08 mol intermediate 1, 0.09 mol phloroglucinol, 70 ml sodium carbonate solution with a mass fraction of 50% and 130 ml dimethyl sulfoxide were added into a container, stirred, and reacted at a temperature of 55° C. for 3 h. After the reaction was completed, the organic layer was separated with a separatory funnel, and the intermediate 2 was obtained by rotary evaporation;

[0045] Step 3, add 0.07 mol intermediate 2 and 13.5 ml concentrated sulfuric acid into a container, stir, and react at 170° C. for 3 h. After the reaction is completed, rotary evaporation is performed to obtain intermediate 3;

[0046] Step 4, add 37.5 ml of toluene, 0.05 mol of intermediate 3 and 1 ml of platinum complex into a container, stir, heat to 110°C, add 0.05 mol of dimethoxymethylsilane, react at 140°C for 1 hour, and obtain the composite functional agent by rotary evaporation.

[0047] Example 3

[0048] The composite functional agent is prepared by the following steps:

[0049] Step 1, 0.11 mol phloroglucinol, 0.1 mol epichlorohydrin and 180 ml dimethyl sulfoxide are added into a container, stirred, reacted at 60° C. for 5 h, and after the reaction, rotary evaporation is performed to obtain intermediate 1;

[0050] Step 2, 0.08 mol of intermediate 1, 0.1 mol of phloroglucinol, 70 ml of 50% sodium carbonate solution and 130 ml of dimethyl sulfoxide were added into a container, stirred, and reacted at 60° C. for 3 h. After the reaction was completed, the organic layer was separated by a separatory funnel, and the intermediate 2 was obtained by rotary evaporation;

[0051] Step 3, adding 0.07 mol intermediate 2 and 15 ml concentrated sulfuric acid into a container, stirring, reacting at a temperature of 170° C. for 3 h, and after the reaction, rotary evaporation to obtain intermediate 3;

[0052] Step 4, add 40 ml toluene, 0.05 mol intermediate 3 and 1 ml platinum complex into a container, stir, heat to 110°C, add 0.05 mol dimethoxymethylsilane, react at 140°C for 1 hour, and rotary evaporate to obtain the composite functional agent.

[0053] Comparative Example 1

[0054] This comparative example is an antioxidant sold by Jiangsu Xinluda Polymer Materials Co., Ltd.;

[0055] 0.6g of the composite functional agent of Examples 1-3 and the antioxidant of Comparative Example 1 were respectively mixed with 9.2g of hydroxy acrylic resin and then applied on a glass plate. The glass plate added with Example 1 was named No. 1, the glass plate added with Example 2 was named No. 2, the glass plate added with Example 3 was named No. 3, and the glass plate added with Comparative Example 1 was named No. 4. The water contact angles of the glass plates No. 1-4 were tested using a POWEREACH JC2000D1 contact angle meter from Shanghai Zhongchen. After the test, the glass plates No. 1-4 were placed in a box-type resistance furnace and subjected to an oxidation weight gain experiment for 4h at a temperature of 80°C. The oxidation weight gain was recorded for 4h. The test results are shown in Table 1:

[0056] Table 1

[0057] project Water contact angle (°) <![CDATA[4h oxidation weight gain (mg / mm 2 )]]> Glass Plate No. 1 111 <![CDATA[0.324X10 -3 mg / mm 2 ]]> Glass Plate No. 2 113 <![CDATA[0.301X10 -3 mg / mm 2 ]]> Glass Plate No. 3 109 <![CDATA[0.343X10 -3 mg / mm 2 ]]> Glass Plate No. 4 69 <![CDATA[0.863X10 -3 mg / mm 2 ]]>

[0058] It can be seen from Table 1 that the water contact angle of glass plates No. 1-3 coated with the hydroxyl acrylic resin added with the composite functional agent obtained in Examples 1-3 is much larger than that of glass plate No. 4 without the composite functional agent added, and is greater than 90°, indicating that glass plates No. 1-3 are hydrophobic and the composite functional agent has good hydrophobic effect. The 4h oxidation weight gain of glass plates No. 1-3 coated with the hydroxyl acrylic resin added with the composite functional agent obtained in Examples 1-3 is less than that of glass plate No. 4 without the composite functional agent added, indicating that the composite functional agent has good antioxidant properties.

[0059] Example 4

[0060] A nano-improved black automobile coating comprises the following raw materials in parts by weight: 62 parts of hydroxy acrylic resin, 1.8 parts of high-pigment carbon black, 1.8 parts of dispersant, 23 parts of mixed solvent, 6 parts of cellulose acetate butyrate, 4 parts of composite functional agent, 0.1 parts of defoamer, 0.1 parts of leveling agent, 0.8 parts of thickener, and 1 part of nano silicon dioxide;

[0061] The preparation method of the nano-improved black automobile coating comprises the following steps:

[0062] The first step is to weigh each raw material according to the mass fraction;

[0063] The second step is to stir the nano-silicon dioxide, dispersant, composite functional agent and mixed solvent at a speed of 400 r / min for 10 min, and then add them to a high-speed oscillator with an oscillation frequency of 640 times / min and oscillate for 60 min to obtain a nano-silicon dioxide dispersion; wherein the dispersant is EFKA4310 and the mixed solvent is butyl acetate;

[0064] The third step is to add nano-silica dispersion, high-pigment carbon black, hydroxy acrylic resin, cellulose acetate butyrate, defoamer, and leveling agent into a dispersion tank at a speed of 900 r / min for 45 minutes, and mix them evenly to obtain a nano-composite liquid; wherein the high-pigment carbon black is Orilon FW255, the defoamer is BYK-088, and the leveling agent is Hemmingsdeqian 837;

[0065] The fourth step is to add the thickener into the nano-composite liquid, and stir and mix at a speed of 150 r / min for 15 minutes to obtain the nano-improved black automobile coating.

[0066] Example 5

[0067] A nano-improved black automobile coating comprises the following raw materials in parts by weight: 73 parts of hydroxy acrylic resin, 2.2 parts of high-pigment carbon black, 2.2 parts of dispersant, 27 parts of mixed solvent, 6 parts of cellulose acetate butyrate, 4 parts of composite functional agent, 0.1 parts of defoamer, 0.1 parts of leveling agent, 0.8 parts of thickener, and 1 part of nano silicon dioxide;

[0068] The preparation method of the nano-improved black automobile coating comprises the following steps:

[0069] The first step is to weigh each raw material according to the mass fraction;

[0070] The second step is to stir the nano-silicon dioxide, dispersant, composite functional agent and mixed solvent at a speed of 400 r / min for 12.5 min, and then add them to a high-speed oscillator with an oscillation frequency of 650 times / min and oscillate for 67.5 min to obtain a nano-silicon dioxide dispersion; wherein the dispersant is EFKA4310 and the mixed solvent is xylene;

[0071] The third step is to add nano-silica dispersion, high-pigment carbon black, hydroxy acrylic resin, cellulose acetate butyrate, defoamer, and leveling agent into a dispersion tank at a speed of 950 r / min for 52.5 minutes, and mix them evenly to obtain a nano-composite liquid; wherein the high-pigment carbon black is Orilon FW200, the defoamer is BYK-054, and the leveling agent is Hemmingsdeqian 837;

[0072] The fourth step is to add the thickener into the nanocomposite liquid, and stir and mix at a speed of 150 r / min for 20 minutes to obtain the nano-improved black automobile coating.

[0073] Example 6

[0074] A nano-improved black automobile coating comprises the following raw materials in parts by weight: 62 parts of hydroxy acrylic resin, 1.8 parts of high-pigment carbon black, 1.8 parts of dispersant, 23 parts of mixed solvent, 8 parts of cellulose acetate butyrate, 6 parts of composite functional agent, 0.3 parts of defoamer, 0.3 parts of leveling agent, 1.5 parts of thickener, and 3 parts of nano silicon dioxide;

[0075] The preparation method of the nano-improved black automobile coating comprises the following steps:

[0076] The first step is to weigh each raw material according to the mass fraction;

[0077] The second step is to stir the nano-silicon dioxide, dispersant, composite functional agent and mixed solvent at a speed of 400 r / min for 15 min, and then add them to a high-speed oscillator with an oscillation frequency of 660 times / min and oscillate for 60 min to obtain a nano-silicon dioxide dispersion; wherein the dispersant is EFKA4310 and the mixed solvent is propylene glycol methyl ether acetate;

[0078] The third step is to add nano-silica dispersion, high-pigment carbon black, hydroxyl acrylic resin, cellulose acetate butyrate, defoamer, and leveling agent into a dispersion tank with a rotation speed of 1000 r / min for 60 minutes, and mix them evenly to obtain a nano-composite liquid; wherein the high-pigment carbon black is Columbia Carbon Black 5000, the defoamer is BYK-088, and the leveling agent is Hemmingsdeqian 837;

[0079] The fourth step is to add the thickener into the nano-composite liquid, and stir and mix at a speed of 150 r / min for 25 minutes to obtain the nano-improved black automobile coating.

[0080] Comparative Example 2

[0081] This comparative example is a water-based automotive coating sold by Hebei Kefeng Water-based Paint Co., Ltd.

[0082] Comparative Example 3

[0083] The composite functional agent in the second step of Example 4 was removed, and the remaining steps remained unchanged.

[0084] The improved black automobile coatings of Examples 4-6, the water-based automobile coating of Comparative Example 2 and Comparative Example 3 were subjected to mechanical property tests. The test results are shown in Table 2:

[0085] Table 2

[0086]

[0087]

[0088] It can be seen from Table 2 that the improved black automobile coatings of Examples 4-6 are far superior to the water-based automobile coatings of Comparative Example 2 and Comparative Example 3 without the composite functional agent of the present invention in terms of mechanical properties, indicating that the addition of the composite functional agent of the present invention can effectively improve the mechanical properties of the automobile coating, and can convert the hydroxyl acrylic resin from hydrophilic to hydrophobic, greatly improving the anti-fouling ability, and having antioxidant properties and not easy to age and lose gloss, so it can be widely promoted and applied.

[0089] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A nano-modified black automotive coating, characterized in that: The invention comprises the following raw materials in parts by weight: 62-73 parts of hydroxy acrylic resin, 1.8-2.2 parts of high-color carbon black, 1.8-2.2 parts of dispersant, 23-27 parts of mixed solvent, 6-8 parts of cellulose acetate butyrate, 4-6 parts of composite functional agent, 0.1-0.3 parts of defoamer, 0.1-0.3 parts of leveling agent, 0.8-1.5 parts of thickener, and 1-3 parts of nano silicon dioxide; The preparation method of the composite functional agent comprises the following steps: Step 1, adding phloroglucinol, epichlorohydrin and dimethyl sulfoxide into a container, and reacting at 60° C. for 5 hours to obtain intermediate 1; Step 2, adding intermediate 1, phloroglucinol, sodium carbonate solution and dimethyl sulfoxide into a container, reacting at a temperature of 50-60° C. for 3 hours to obtain intermediate 2; Step 3, adding intermediate 2 and concentrated sulfuric acid into a container, reacting at 170° C. for 3 h to obtain intermediate 3; Step 4, adding toluene, intermediate 3 and platinum complex into a container, heating to 110° C., adding dimethoxymethylsilane thereto, and after completion of the dropwise addition, reacting at a temperature of 140° C. for 1 h to obtain the composite functional agent; The amount ratio of phloroglucinol, epichlorohydrin and dimethyl sulfoxide used in step 1 is 0.1-0.11 mol:0.1 mol:150-180 ml; In step 2, the sodium carbonate solution is a sodium carbonate aqueous solution with a mass fraction of 50%, and the amount ratio of the intermediate 1, phloroglucinol, sodium carbonate solution and dimethyl sulfoxide used is 0.08 mol: 0.08-0.1 mol: 70 ml: 130 ml.

2. A nano-modified black automotive paint according to claim 1, characterized in that: The concentrated sulfuric acid in step 3 is a sulfuric acid aqueous solution with a mass fraction of 98%, and the amount ratio of the intermediate 2 to the concentrated sulfuric acid is 0.07 mol: 12-15 ml.

3. A nano-modified black automotive paint according to claim 1, characterized in that: The amount ratio of toluene, intermediate 3, platinum complex and dimethoxymethylsilane used in step 4 is 35-40 ml: 0.05 mol: 1 ml: 0.05 mol.

4. A nano-modified black automotive paint according to claim 1, characterized in that: The high-pigment carbon black is one of Orion FW255, Orion FW200, and Columbia Carbon Black 5000; the dispersant is EFKA4310; the mixed solvent is one of butyl acetate, xylene, and propylene glycol methyl ether acetate; the thickener is Hemmings WT-105; the defoamer is one of BYK-088 and BYK-054; and the leveling agent is Hemmings Deqian 837.

5. A method for preparing the nano-modified black automotive coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: The first step is to weigh each raw material according to the mass fraction; The second step is to stir and mix the nano-silicon dioxide, dispersant, composite functional agent and mixed solvent, and then add them into a high-speed oscillator for oscillation to obtain a nano-silicon dioxide dispersion; The third step is to add the nano-silica dispersion, high-pigment carbon black, hydroxy acrylic resin, cellulose acetate butyrate, defoamer, and leveling agent into a dispersion tank and mix them evenly to obtain a nano-composite liquid; The fourth step is to add the thickener into the nano composite liquid, stir and mix to obtain the nano improved black automobile coating.

6. The method for preparing a nano-modified black automobile coating according to claim 5, characterized in that: In the second step, the stirring time condition is 10-15 min, the stirring speed is 400 r / min, the high-speed oscillation time condition is 60-75 min, and the high-speed oscillation frequency is 640-660 times / min.

7. The method for preparing a nano-modified black automobile coating according to claim 5, characterized in that: In the third step, the speed of the dispersion cylinder is set to 900-1000r / min, and the dispersion time in the dispersion cylinder is 45-60min.

8. The method for preparing a nano-modified black automobile coating according to claim 5, characterized in that: The stirring speed of the nanocomposite liquid is 150 r / min, and the stirring time is 15-25 min.

Citation Information

Patent Citations

  • Environment-friendly automobile coating and preparation process thereof

    CN110373054A

  • Corrosion-resistant epoxy dresin coating and preparation method thereof

    CN113736349A